2015
DOI: 10.1055/s-0034-1393331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes following stent placement in refractory benign esophageal stricture: a systematic review and meta-analysis

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 20 publications
(38 reference statements)
5
94
1
2
Order By: Relevance
“…No major complications, including massive bleeding, perforation or fatal infection were observed. Conversely to previous studies (27,28), no migration of the stents were observed in the present study. This may be due to the fact that stents with larger diameters were used, which enhanced the radical focus of the esophagus.…”
Section: Discussioncontrasting
confidence: 99%
“…No major complications, including massive bleeding, perforation or fatal infection were observed. Conversely to previous studies (27,28), no migration of the stents were observed in the present study. This may be due to the fact that stents with larger diameters were used, which enhanced the radical focus of the esophagus.…”
Section: Discussioncontrasting
confidence: 99%
“…EBD should have been considered before the esophageal stricture progressed to obstruction. Though an esophageal stent have been reported to be useful for refractory benign esophageal stricture [14, 15], there is a report that an esophageal stent placement itself can be a risk factor related to AEN [16], and no report about successful stent placement for esophageal stricture after AEN. Therefore, stent treatment for esophageal stricture after AEN still remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials assessing the efficacy of FCSEMS and SEPS had suboptimal long-term outcomes. A recent meta-analysis 8 regarding the treatment efficacy of FCSEMS, SEPS and BD stents in refractory benign strictures, found an overall clinical success rate of 40.5 % when all treatment modalities were considered. The differences in the success rates between the various modalities were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these, the optimal injection technique as well as the frequency and dose of steroids to be used are yet to be established 5. Removable plastic (SEPS) or fully covered metal self-expanding stents (FCSEMS) have also been tried, but initial positive results were not replicated 6 7 and a recent meta-analysis reported significant migration rates and mediocre success rates overall 8. …”
Section: Introductionmentioning
confidence: 99%